Motive to achieve a theoretical justification of its structural components - Артюшенко [Aleksandr Artyushenko] Олександр Федорович; Нечипоренко [Denis Nechyporenko] Денис Леонидович (Slobozhanskyi Herald of Science and Sport, 2013)
Discusses various views on authors understanding of the nature motif. Shows examples of classification of motives. Studied the relationship of the level of aspiration, self-esteem and achievement motivation. Based on the studied material formed of “achievement motive” that understand how the relentless pursuit, encouraging people to activities associated with efforts to succeed (or avoid failure) in the activity and which depends on the level of individual claims. Analyzed psychological and pedagogical literature which theoretically allowed reasoning structural components and indicators of achievement motive, which allow to objectively assess the level of formation of the motive